User's Guide to Coursewriter II Preprocessor, VI. 2. Systems Memo Number Three - Mitchell, Ron.; Conner, Michael; Texas Univ., Austin. Computer-Assisted Instruction Lab. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Procedures are presented to assist programers with the use of the Coursewriter II preprocessor. The preprocessor was designed to reduce the repetition of effort which takes place from the conception of a course by its author to the time of its use by students in on-line instruction. It accomplishes this by relieving the programer of the tedious task of translating planning guides into Coursewriter II statements, allowing him to concentrate upon program logic. Topics covered in this manual include code descriptions, variable reference, error messages and recovery, coding conventions, job submission, output, course assembly, and malfunctions. A sample problem and a glossary of terms are appended. (PB)
Sponsoring Agency: National Science Foundation, Washington, DC.
ERIC Note: See also EM 011 700 and EM 011 701.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Programs; Computer Science; Guides; Programers; Programing; Coursewriter Programing Language